Particulate matter exposure exacerbates cellular damage by increasing stress granule formation in respiratory syncytial virus-infected human lung organoids. (15th December 2022) - Choi, Sunkyung; Kim, Eun-Mi; Kim, Seung-Yeon; Choi, Yeongsoo; Choi, Seri; Cho, Namjoon; Park, Han-Jin; Kim, Kee K.
Abstract: Exposure to atmospheric particulate matter (PM) increases morbidity and mortality in respiratory diseases by causing various adverse health effects; however, the effects of PM exposure on cellular stress under virus-infected conditions remain unclear. The effects of PM under 10 μm (PM10 ) and diesel PM (DPM) on respiratory syncytial virus (RSV) infection were investigated in human two-dimensional lung epithelial cells and human three-dimensional lung organoids mimicking the lung tissue. We evaluated the formation of stress granules, which are important in cellular adaptation to various stress conditions. Furthermore, we investigated the effects of repeated exposure to PM10 and DPM on DNA damage and cell death during viral infection. PM10 and DPM did not cause stress granule formation in the absence of RSV infection but drastically increased stress granule formation and signal transduction during RSV infection in human lung epithelial cells and human lung organoids. Further, repeated exposure to PM10 and DPM caused cell death by severely damaging DNA under RSV infection conditions. Thus, PM10 and DPM induce severe lung toxicity under stress conditions, such as viral infection, suggesting that the effects of PMs under various stressful conditions should be examined to accurately predict the lung toxicity of PM. Graphical abstract: Image 1 Highlights: PM10 and DPM increase cytotoxicity under stress conditions. PM10 and DPM increase SG formation under viral infection conditions. PM10 and DPM induce severe lung toxicity under RSV infection conditions. PM10 and DPM induce SG formation via PKR/eIF2α pathway under RSV infection conditions.